“We talk about it in private”. A cross-sectional study of cultural attitudes and health-seeking practices among perimenopausal University staff in Bayelsa, Nigeria. - Angaye, Ukie; Scent, Grace A.T.; Sibiri, Elliot A. (Student's Journal of Health Research Africa, 2025)
Background Despite increasing recognition of women’s midlife health challenges, the intersection of cultural norms and healthcare access during perimenopause remains underexplored in Nigeria’s academic settings. This study explores how cultural attitudes shape health-seeking practices among perimenopausal university staff in Bayelsa, Nigeria. Methods Using a mixed-methods design, the study surveyed 313 academic and non-academic female staff aged 40–55 across two public universities. Quantitative data were analyzed using descriptive statistics and chi-square tests, while qualitative data from in-depth interviews were thematically examined. Results Findings reveal that cultural norms significantly influence women’s willingness and ability to seek professional medical care during perimenopause. About 40.9% of respondents perceived cultural norms as moderately affecting their health-seeking behaviour, while 23.3% reported a significant influence. Chi-square analyses showed statistically significant associations between cultural perceptions, discussion openness, comfort with healthcare providers, and professional health-seeking patterns (p < 0.001). Qualitative narratives highlight both supportive and stigmatizing cultural contexts. Some women expressed comfort discussing menopause due to familial openness, while others cited stigma and fear of being perceived as old or weak as reasons for silence. Additionally, preferences for private healthcare stemmed from dissatisfaction with public hospital services, despite cost barriers. Conclusions The study emphasizes the need for culturally sensitive and gender-responsive healthcare services tailored to the needs of perimenopausal female professionals. Recommendations Health education programs should address stigma, negative cultural attitudes, poor health-seeking behaviour, and also foster open conversations about perimenopause, particularly within university institutions.